The Role of Phyllosphere Bacteria in Improving Cotton Growth and Yield Under Drought Conditions - Sharath, S.; Triveni, S.; Nagaraju, Y.; Latha, P. C.; Vidyasagar, B. (Frontiers in Agronomy, 2021)
Cotton is a valuable fiber and cash crop in Telangana, India; however, crop growth and fiber yield were affected by the uneven distribution of rainfall. The cotton phyllosphere bacterial isolates were isolated from Rangareddy and Warangal Districts of Telangana and obtained 31 phyllosphere bacterial isolates. These isolates were screened for drought tolerance and found that fifteen suitable isolates grew at -1.25 Mpa stress level with copious amounts of exopolysaccharides production. These isolates were further screened for ACC deaminase production and observed 0.13 to 0.40 mM of α-ketobutyrate per milligram of cellular protein per hour. Five efficient bacterial isolates namely Pseudomonas stutzeri, Acinetobacter sp., Bacillus mojavensis, Pseudomonas chlororaphis, and Enterobacter asburiae were found to produce ACC deaminase and able to grow at -1.25 Mpa stress level. The cotton variety ADB-542 (drought susceptible) was treated with drought-tolerant five isolates. Acinetobacter sp. treated seeds had the highest seed germination and seedling vigour of 76.67 % and 45.81 %, respectively. The nutrient status of inoculated plots was considerably improved. The root length, fresh weight, proline content, and the number of bolls were increased by 28.52, 41.9 28.78, and 12.99 %, respectively, with the inoculation of Acinetobacter sp., to plants at -0.75 Mpa water potential. Overall the performance of cotton was improved significantly with the inoculation of phyllosphere bacteria to seeds; hence they can be recommended for the application of field crops as bio-inoculants.